2018
DOI: 10.5114/aic.2018.79194
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of biodegradable polymer-coated thin strut sirolimus-eluting stent vs. durable polymer-coated everolimus-eluting stent in patients with acute myocardial infarction

Abstract: IntroductionThe biodegradable polymer drug-eluting stents were developed to improve vascular healing. However, further data are needed to confirm the safety and efficacy of these stents in patients with acute myocardial infarction (AMI).AimWe sought to determine the 1-year clinical follow-up in patients with AMI treated with a thin strut biodegradable polymer-coated sirolimus-eluting stent (BP-SES) versus a durable coating everolimus-eluting stent (DP-EES).Material and methodsWe analyzed patients with AMI (STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There is considerable clinical evidence supporting the use of new‐generation DES in patients with acute MI, including STEMI 20‐22,28‐31 . Yet, up to now, clinical outcome data >1 year after treatment with RO‐ZES in patients with acute MI are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable clinical evidence supporting the use of new‐generation DES in patients with acute MI, including STEMI 20‐22,28‐31 . Yet, up to now, clinical outcome data >1 year after treatment with RO‐ZES in patients with acute MI are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable clinical evidence supporting the use of new‐generation DES in patients with acute MI, including STEMI. 20 , 21 , 22 , 28 , 29 , 30 , 31 Yet, up to now, clinical outcome data >1 year after treatment with RO‐ZES in patients with acute MI are scarce. The Korean Acute MI Registry 32 assessed the short‐term clinical outcome of 1,486 acute MI patients who were treated with either RO‐ZES ( n = 402) or everolimus‐eluting stents ( n = 1,084).…”
Section: Discussionmentioning
confidence: 99%
“…The expectation from DES is a decrease in ISR through inhibition of smooth muscle and endothelial proliferation. Although experience described in the coronary literature largely supports such practice, DES I in cardiac procedures have been found to be associated with clot formation in some cases, resulting in thrombosis at the stent site [10, 19]. Recently, second generation DES were introduced with the scope to overcome the limitations of the first generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…The BP-SES used in this study is a Conformité Européenne (CE)-approved balloon expandable cobalt-chromium stent with a 71 microns strut thickness covered with a biodegradable copolymer of poly-lactic and glycolic acid together with sirolimus. In a previously published study, BP-SES demonstrated comparable safety and efficacy in all-comers and acute myocardial infarction (MI) patient population when compared to the benchmark balloon-expandable cobalt-chromium DP-EES [15,16]. DP-EES was previously granted the specific indication for DM patients from the Food and Drug Administration of the United States and CE mark from the European Commission.…”
Section: Stent System Descriptionmentioning
confidence: 99%